Operasional Baitul Mal Wa Tamwil (Bmt) Dalam Pemberdayaan Ekonomi Umat Di Kabupaten Sidoarjo - Moch. Khoirul Anwar (Jurusan Akuntansi Fakultas Ekonomi Universitas Negeri Surabaya, 2013)
AbstractOne of the efforts to empower peoples economy is the existence of microfinance institutions such as Bayt al-Mal wa al-Tamwil (BMT) which have role to establish the economy successfully. This research used a qualitative approach and the type was field research. Data obtained in this research through participatory observation and interviews involved. The findings of this research can be presented that BMT has a participation in the economic empowerment of small and micro entrepreneurs. However, BMT in Sidoarjo Regency, it can not perform its function as bayt al-mal, having a duty to apply the social mission.